INFLUENCE OF INTERACTIVE INSTRUCTION APPROACH IN ENHANCING CURRICULUM DELIVERY AT TERTIARY INSTITUTIONS IN IMO STATE - Chuka-Okonkwo, Ogechi (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the influence of an interactive instruction approach in enhancing curriculum delivery in tertiary institutions in Imo State. The approach included the use of interactive boards, web 2.0 tools and other ICT-related facilities. Both qualitative and quantitative approaches were used. An analytical survey design was adopted through the use of structured interviews and obtrusive observation. A sample of 50 teacher educators comprising 34 females and 16 males was randomly selected from two purposively sampled tertiary institutions in Imo State. The content analysis approach was used to analyse the responses at both the descriptive and interpretative levels to answer the research questions, while the chi-square test was used to test the three (3) hypotheses of the study at an error level of 0.05. The results revealed that an insignificant proportion of the respondents had knowledge and could use the interactive instruction method. Results also revealed that acquisition does not significantly depend on gender or school but significantly depends on age. It was recommended that all teacher-educator institutions urgently procure and install interactive teaching facilities and train educators accordingly.